BASIC GUIDELINES FOR A SUCCESSFUL IMPLANTATION OF THE ACTIVITY BASED COSTING (ABC) - Carrión Nin, José (2005)
This article seeks to establish a practice guide of the main steps to follow, showing experiences and giving suggestions to the one pretending to implement an Activity Based Costing. Implementation of ABC requires a complex and analytical process that is expensive and timeconsuming, that is why managers may want to be sure of the advantages before embarking upon the implementation of ABC.